Biological Synthesis of Chiral p‐Coumaroyl Glycerol. (15th May 2019) - Song, Min Kyung; Sim, GeunYoung; Lee, Su Jin; Kim, Bong‐Gyu; Kim, Mihyang; Lee, Taegum; Chong, Youhoon; Ahn, Joong‐Hoon
Abstract : Escherichia coli harboring Os4CL and OsHCT4 was used to synthesize ( S )‐ p ‐coumaroyl glycerol.